Treatment outcome and associated factors of patients with atrial fibrillation in adult emergency rooms of selected hospitals of Addis Ababa, Ethiopia: A one-year cross-sectional study - Surafel Desalegn; Biruktawit Zemede; Feven Tedla; Tewodros Getnet; Bisrat Tamene Bekele; Eyerusalem Kebede Zewde; Damena mulatu; Teklegiorgis Goshime; Bikis liyew; Kassaye Demeke Altaye (PLoS ONE, 2025)
Background Atrial fibrillation is the most common sustained cardiac rhythm disorder with substantial mortality and morbidity from stroke, thromboembolism, heart failure, and impaired quality of life. This study aimed to investigate the emergency presentation, treatment outcome and associated risk factors of atrial fibrillation patients admitted to three tertiary hospitals in Addis Ababa. Methods A cross-sectional study was conducted in the adult emergency room of three tertiary hospitals in Addis Ababa. All atrial fibrillation patients admitted to these hospitals from August 15, 2021, to August 15, 2022, fulfilling inclusion criteria were included in the study. Data was collected by reviewing medical records in the form of a structured data abstraction form and analyzed by SPSS. Result A total of 133 chart records were reviewed and the mean (±SD) age of study participants was 54.82 ± 20.49 years and ranged between 18–85 years of age. The majority of the patients, 47 (35.3%) were aged between 18–40 years. Nearly more than half of the patients 69 (51.9%) were females and two third [91 (68.4%)] of the patients were from Addis Ababa. Patients of the age group 40–59 with atrial fibrillation have an 82% lower chance of developing stroke than those in the age group >60 years and patients with underlying cardiovascular diseases have seven times higher odds of having a stroke compared to those without underlying cardiac diseases. Male patients with atrial fibrillation had 2.15 times higher odds of staying for > 24 hours at the emergency department compared to female patients. The odds of a > 24-hour stay in the ER significantly increased by 2.7 times as the patient became unstable compared to stable patients. Conclusion Males and those with unstable atrial fibrillation have a higher chance of staying more than 24 hours in the emergency room. According to the study, patients who were more than 60 years of age with underlying cardiovascular diseases had a higher likelihood of developing ischemic stroke.